Digestibilidade aparente e energia metabolizável do Juá e da Algaroba para galinhas Isa Label - Souza, Rosângela Fernandes de (Universidade Federal Rural do Semi-Árido, 2017)
Juazeiro (Zizyphus Joazeiro Mart) and Algarobeira (Prosopis Juliflora) trees are considered feasible alternative food to northeast region, due to their wide economic value, fruiting ability even in periods of drought, and good adaptability in semi-arid regions. The objective of this is study was to evaluate the bromatological composition, the apparent digestibility of the rations and the metabolizable energy of the shell and pulp or seed of the fruit of the juazeiro or of the algarobeira pod in rations for adult chickens Isa Label. 20 Isa Label chickens were used, with 104 weeks, distributed in a completely randomized design in a 4x4 factorial (ration x period), one reference diet (RREF) and another three with a replacement of 20% of the reference diet by the shell and pulp of the fruit of the juazeiro or seed of the fruit of the juazeiro or pod of the algarobeira in periods of 7, 14, 21 and 28 days. The chickens were individually housed in metal cages adapted for total collection of excreta, and 200 (g/chickens/day) of feed and water were provided at will. The results for bromatological composition of the algarobeira pod, seed or shell and pulp of the fruit of the juazeiro were, 86,00; 90,50 and 84,45% dry matter (DM), 2,70; 3,50 and 8,30% of mineral matter (MM), 7,20; 3,80 and 8,30% crude protein (CP), 0,35; 1,00 and 0,50% ethereal extract (EE), 40,40; 60,00 and 19,10% neutral detergent fiber (NDF), 24,60; 38,90 and 10,60% acid detergent fiber (FDA). The apparent coefficients digestibility (ACD) of the reference ration (RREF), algae pod (RALG), ration with seed of the juazeiro fruit (RJSE) and ration with shell and pulp of the juazeiro fruit (RJCA) for chickens Isa Label, respectively, were 77,34%; 72,72%; 69,29% and 72,48% for dry matter (DM), 33,65%; 29,37%; 26,40% and 29,96% for mineral matter (MM), 65,26%; 46,60%; 44,67% and 50,25% for crude protein (CP), 88,15%; 81,50%; 80,45% and 81,15% for ethereal extract (EE), 25,30%; 33,00%; 24,60% and 29,95% for neutral detergent fiber (NDF) and 17,00%; 18,60%; 17,25% and 18,10% for acid detergent fiber (ADF) and 83.55%; 80.63%; 79.03% and 80.92% for crude energy digestibility (DEB). In turn, the means of apparent metabolizable energy of said rations were: 2987.66 kcal / kg; 2884.06 kcal / kg; 3153.98 kcal / kg; 2918.18 kcal / kg. However, the values of the reference digestibility (RREF), algarobeira pod ration (RALG), ration with seed of the juazeiro fruit (RJSE) and ration with shell and pulp of the juazeiro fruit (RJCA) 7, 14, 21 and 28 days (collection of excreta) were: 75.35%, 73.54%, 72.17% and 70.78% for dry matter; 32.20%, 30.67% 28.92% and 27.59% for mineral matter; 54.40%, 52.58%, 50.43% and 49.39% for crude protein; 83.44%, 83.05%, 82.57% and 82.19% for ethereal extract; 27.48%, 28.27%, 28.59% and 29.51% for neutral detergent fiber; 16.68%, 17.32%, 18.06% and 18.90% for acid detergent fiber; 80.03%, 82.01%, 82.66% and 79.43% for crude energy and finally 2948.89 kcal / kg, 3021.88 kcal / kg, 3046.47 kcal / kg and 2926.65 kcal / Kg for apparent metabolizable energy of said rations. The substitution in 20% of algarobeira pod, seed or shell and pulp of juazeiro fruit in Isa Label poultry chickens provided a reduction in the digestibility of reference nutrients, as well as of minerals, lipids, proteins and energy in all collection periods. The values of the apparent metabolizable energy of the algarobeira pod, seed or shell and pulp of the fruit of the juazeiro were 1660.00; 1577.00 and 1705.00 kcal / kg respectively
Apparent digestibility and metabolizable energy of Juá and Algaroba meals for Isa Label chickens
Keywords: Digestibilidade; Energia metabolizável; Isa Label; Prosopis juliflora; Zizyphus joazeiro; Digestibility; Metabolizable energy; Isa Label; Prosopis juliflora; Zizyphus joazeiro; CIENCIAS AGRARIAS::MEDICINA VETERINARIA